2017
DOI: 10.1038/s41598-017-12654-3
|View full text |Cite
|
Sign up to set email alerts
|

Broadband reconfigurable logic gates in phonon waveguides

Abstract: The high-quality-factor mechanical resonator in electromechanical systems has facilitated dynamic control of phonons via parametric nonlinear processes and paved the development of mechanical logic-elements. However, the narrow spectral bandwidth of the resonating element constrains the available nonlinear phenomena thus limiting the functionality of the device as well as the switching speeds. Here we have developed phonon waveguides, with a two-octave-wide phonon transmission band, in which mechanical four-wa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 48 publications
0
21
1
Order By: Relevance
“…In this section, we investigate the numerical solutions to the set of advection-reaction equations [Eq. (17)], which resulted from the consideration of multiple time and space scales in the dynamic resonance of the approximate quadratic locally resonant metamaterial. The 1D advection-reaction equations involve first-order derivatives in space and in time.…”
Section: Semianalytical Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this section, we investigate the numerical solutions to the set of advection-reaction equations [Eq. (17)], which resulted from the consideration of multiple time and space scales in the dynamic resonance of the approximate quadratic locally resonant metamaterial. The 1D advection-reaction equations involve first-order derivatives in space and in time.…”
Section: Semianalytical Resultsmentioning
confidence: 99%
“…In these papers, it was shown that nonlinearity induces amplitude-dependent dispersion and group velocity, i.e., demonstrating the tunability potential of nonlinear phononic structures. By making use of this feature, new functionalities have been proposed, such as mechanical switches and logic gates [17], acoustic diodes [18], and acoustic rectifiers [19]. In granular materials, the effect of highly nonlinear interactions has been shown to induce solitary wave propagation [20,21] and discrete breathers [22].…”
Section: Introductionmentioning
confidence: 99%
“…Locally resonant metamaterials operating in the nonlinear regime 9 11 provide even more opportunities for breakthrough applications. Recently, nonlinearities have been exploited in locally resonant granular crystals 12 , 13 or to obtain logic gates 14 and acoustic diodes 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Defect arrays can result in the formation of acoustic metamaterials that are homogenized artificial materials with unprecedented functionalities [4,6]. Similar to electromagnetic wave propagation in photonic crystal structures, the propagation of acoustic modes influenced by these localized defect modes in phononic structures can be designed to realize sensors [7], filters and waveguides [8,9], and acoustic logic elements [10,11] in the ultrasonic frequency domain.…”
Section: Introductionmentioning
confidence: 99%